2021
DOI: 10.28945/4884
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Student Interaction in Distance Learning in Emergency Situations

Abstract: Aim/Purpose: The goal of this study was to examine which of the types of teacher-student interactions found in previous studies by Kang (2009) and Kang and Im (2013) during distance learning in routine situations, were also found in times of emergency, specifically during the COVID-19 pandemic, and whether these interactions differed between students with regard to the extent and nature of each type of interaction. Background: Teacher-student interactions during learning in general and particularly in distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Other crucial studies describe the effectiveness of experiment series with learning resource data sets. The results of the experiment show that the proposed methods are able to give valuable recommendations for appropriate areas of student learning with significantly improved knowledge outcomes in terms of accuracy and efficiency compared to previous similar studies ( Sason and Kellerman 2021 ; Sharpe et al 2019 ; Sinclair et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 80%
“…Other crucial studies describe the effectiveness of experiment series with learning resource data sets. The results of the experiment show that the proposed methods are able to give valuable recommendations for appropriate areas of student learning with significantly improved knowledge outcomes in terms of accuracy and efficiency compared to previous similar studies ( Sason and Kellerman 2021 ; Sharpe et al 2019 ; Sinclair et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 80%
“…Similarly, through a large-scale online survey across the world, Aristovnik et al highlighted the need for online educators to ensure that professors possess the necessary knowledge and skills for virtual instruction and have the appropriate ICT equipment [ 3 ]. Distance learning studies in Israel and Turkey have also emphasized the importance of teacher-learner interactions in promoting learning, yet virtual education poses challenges because instructors lack nonverbal feedback [ 40 , 41 ]. Goodwin et al in Ireland reported that challenging online interactions reduced the quality of learning for nursing students [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The others, forget to turn off the camera, you see them lying down and not conditioned to learn." (Participant 10) Except when students actively choose to connect and ask questions, it can be challenging for professors to tell when their pupils are lost or confused in an online environment [65]. In addition, academic integrity continues to be a problem.…”
Section: Remote Teaching and Impact On Assessment Procedures Vs Face-...mentioning
confidence: 99%